A129: Analysis of Igf axis in development of HCC. Issue 1 (November 2015) - Dashenkova, N.; Mikaelyan, A.
Abstract: IGF signaling pathway plays an important role in the regulation of cell growth, proliferation, differentiation, apoptosis and survival. Deregulation of this pathway has been frequently identified in the development of hepatocellular carcinoma (HCC). IGF signaling pathway consists of IGF ligands (IGF-I and IGF-II), IGF binding proteins (IGFBP 1-7), and membrane-bound IGF receptors (IGF-1R, IGF-II/M6PR, and IGF-2R). The insulin-like growth factor binding proteins (IGFBPs) have several functions, such as IGF transporting, accumulation of IGF at the specific cell pools, inhibition and activation of ligand–receptor interaction. Furthermore, the Igfbps may act independently of IGF-pathway. Diethylnitrosamine (DEN) was used for induction of hepatic tumorigenesis. The male mice, 2 weeks old, were injectedintraperitoneally with 20 mg/kg body weight of DEN. The liver tissue samples were collected 4, 6, 8, 12 months after injection. We performed a comprehensive histological analysis of all kinds of liver samples: tumors, tumor surrounding tissue and normal tissue. Dysplasia was observed 4 months after injection, at hepatocellular adenomas were identified 6–8 months after injection. In the experimental group, 100% of mice had multifocal HCC 12 months after injection. Evaluation of samples from the control group showed normal liver architecture and histology. Western blot analysis showed the presence the HCC tumor marker alfa-fetoprotein only in tumor samples. High levels of Igf-1R and FoxO3 proteins were observed in tumor tissue in contrast to the surrounding and normal tissues 12 months after injection. The expression profiles of Igfbp-1, -2, -3, -4, -5, -6, -7, Igf-1R, FoxO3 were analyzed by real time PCR. The most significant results were observed 8 and 12 months after DEN injection. RT-PCR showed the dynamic increase in Igf-1R expression in tumor. Expression pattern of Igfbps has shown a high level of Igf-1, -2, -5, -6, -7 mRNA in surrounding tissue and Igfbp-1, -3, -5 in tumor compared to control. The expression of Igfbp-2, -4, -5, -6, -7 was up-regulated, whereas expression of Igfbp-1, -3 was down-regulated in surrounding tissue. The expression of Igfbp-4 was decreased in tumor samples. The expression levels of Igfbp-3, -4 in surrounding tissue and Igfbp-7 in tumor were the same as in the control. We detected high level of mRNA of FoxO3 in tumor. In conclusion, these data confirm previously existing assumption about paracrine effect of Igfbps on tumor growth and progression. Phosphorylation of FoxO3 protein may play an important role in survival of cancer cells. Our results showed up-regulation of Igfbp-2 and Igfbp-5 in tumor and tumor surrounding tissue. Igfbp-2 and Igfbp-5, well known activators of Igfs, can be pro-tumorigenic factors, which are important for hepatocarcinogenesis. Hence, therapeutic targeting of these proteins may offer options for intervention in human HCC. Project supported byRussian Foundation for Basic Research (Russia) No. (113-04-01459).